EVALUATION OF SOME MULBERRY VARIETIES FOR YIELD AND QUALITY THROUGH BIOASSAY IN MANIPUR, NORTH EAST INDIA - DEBARAJ, Y.; SINGH, RAVINDRA; BAJPAI, A. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
Eight mulberry varieties, viz., BC259, K2, S1, S146, S1635, TR4, TR10 and V1 were studied for their leaf yield and rearing performance in Manipur. Out of these varieties, V1 has yielded significantly highest leaf yield followed by S1635 and S146 respectively and the yield of BC259, K2, TR10 and TR4 being at pat. The lowest leaf yield was recorded in S1. Bioassay conducted through silkworm rearing revealed that the highest cocoon yield (both by weight and number) was recorded in V1 followed by BC259, S1635, K2 and S1. Among these, S1 and S1635 showed higher cocoon shell percentage while BC259 showed higher cocoon weight. Hence, V1, S1635, BC59, K2 and S1 are equally good in leaf and cocoon yield and are superior to other varieties of mulberry tested.